“Cultural” hate speech and the fall of Yugoslavia – discourse analysis of the selected aspects - Pilarska, Justyna (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
This article tackles the issue of written and spoken propaganda in Serbian and Croatian realms of culture and media proceeding the fall of Yugoslavia at the beginning of the 1990s. It makes two pieces of writing a point of departure for further analysis, i.e. Dubravka Ugrešić’s “The Culture of Lies”, and Ivan Čolović’s “The Balkans: The Terror of Culture: Essays in Political Anthropology”. By so, the article attempts to reveal the banality and brutality of nationalism and the way that nationalistic ideology permeated science, culture and media, involving the conformity of intellectuals, propaganda and censorship, followed by the strategies of human manipulation. The subject of analysis embraces the use of the Serbian and Croatian state-run mass media, anthropological discourse and other written forms of deconstruction of the social order, shortly before and following the fall of Yugoslavia.
Keywords: Croatia; culture; fall of Yugoslavia; discourse analysis; hate speech; nationalistic propaganda; Serbia